Identification of Discrete Polyadenylate-containing RNA Components Transcribed from HeLa Cell Mitochondrial DNA - Ojala, Deanna (1974)
Polyacrylamide gel electrophoresis and sedimentation analysis under denaturing conditions of poly(A)-containing RNA from the polysome region of the sedimentation pattern of a HeLa-cell mitochondrial lysate has revealed the occurrence of a discrete RNA component, which sediments in the native state with a sedimentation constant of about 7 S. From the sedimentation behavior under native and denaturing conditions and the poly(A) content, a molecular weight of about 9 × 10(4) has been estimated for this component. RNA·DNA hybridization experiments have indicated that this component is coded for by the light strand of mitochondrial DNA. Evidence for the occurrence of a poly(A)-containing RNA component sedimenting at about 9 S and coded for by the heavy strand has also been obtained.